PENGARUH BRAND AMBASSADOR TWICE, KUALITAS PRODUK DAN BRAND TRUST TERHADAP KEPUTUSAN PEMBELIAN PRODUK SCARLETT WHITENING (STUDI PADA MAHASISWA DI KOTA MEDAN) - Nurul Azzura; Ainun Mardhiyah (Transpublika Publisher, 2023)
One of the needs that has been considered important in today's era is the need for skin care. One of the famous skincare brands is Scarlett Whitening. Seeing the rise of skin care and beauty manufacturers, the Scarlett Whitening brand carried out a business strategy by attracting South Korean girl group TWICE as a brand ambassador. This study aims to determine the influence of TWICE's brand ambassador, product quality, and brand trust on purchasing decisions on Scarlett Whitening products with a research on students in the city of Medan. The influence of the three independent variables on the dependent variable is processed and analyzed partially and simultaneously. The form of research used in this study is quantitative research. Research sampling using purposive sampling techniques with 100 respondents as samples. The primary data of this study were obtained by distributing questionnaires, and secondary data were obtained from literature studies. The data analysis methods used are instrument tests, classical assumption tests, multiple linear regression analysis, and hypothesis tests. The results showed that TWICE's Brand Ambassador variable had no effect on the Purchase Decision variable. Meanwhile, Product Quality and Brand Trust variables have a significant effect on Purchasing Decisions. In the simultaneous test, the three independent variables had a significant effect together on the Purchase Decision variable with a Ftable value of 2.70 (52.726 > 2.70) and a Sig. value of 0.000 < 0.05 and an influence level of 61.1% and the remaining 38.9% was influenced by factors outside this study